Student Translation Process in Narrative Text Learning in Vocational High Schools: Proses Penerjemahan Siswa Dalam Pembelajaran Teks Naratif Di Sekolah Menengah Kejuruan - Mochammad Ogan Dony Mayuky; Fika Megawati (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to determine the types of translation techniques used by SMK Yapalis Krian class X AK 3 students in Narrative text section of the english class. Narrative texts were chosen because they contain stories with a chronological sequence that are interconnected and come in a variety of genres, allowing students to translate and work on the Narrative text problems in a variety ways. This study employs a descriptive design, with data collected through observation and the subject filling out a questionnaire page online. Data were taken from students of class X AK 3 SMK Yapalis Krian. The findings show that students use the methods of analysis, transfer and restructuring sequentially. Students who do not use appropriate stages and only use one or two stages as the second most common translation process.